2016
DOI: 10.1016/j.drugalcdep.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Trends in registered medical marijuana participation across 13 US states and District of Columbia

Abstract: Participation in MMJ programs varies considerably by state and within states over time. Trends are discussed within the context of federal and state policies, and the availability of marijuana via dispensaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 31 publications
3
96
0
2
Order By: Relevance
“…In this study of individuals who reported cannabis use in the past year, about a sixth of those who reside in states that legalized medical cannabis used cannabis recommended by a medical provider. Although, people who use medical cannabis currently comprise a minority of cannabis users, the number of people using medical cannabis may grow as more time elapses from passage of medical cannabis laws, and as more states legalize medical cannabis (19). Some studies in adults suggest a rise in the number of adults with cannabis use disorders (20), especially in states that have legalized medical cannabis due to the higher prevalence of use in those states (21).…”
Section: Discussionmentioning
confidence: 99%
“…In this study of individuals who reported cannabis use in the past year, about a sixth of those who reside in states that legalized medical cannabis used cannabis recommended by a medical provider. Although, people who use medical cannabis currently comprise a minority of cannabis users, the number of people using medical cannabis may grow as more time elapses from passage of medical cannabis laws, and as more states legalize medical cannabis (19). Some studies in adults suggest a rise in the number of adults with cannabis use disorders (20), especially in states that have legalized medical cannabis due to the higher prevalence of use in those states (21).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 2013-2014 NSDUH because questions regarding medical marijuana use status were included in the survey since 2013. Prior findings suggested that children and adolescents accounted for a very small proportion (< 1%) of medical marijuana users (Fairman et al, 2016). As a result, a total of 15,440 past-year adult marijuana users (2013: n=7,770; 2014: n=7,670) were included for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that, while not all MML states have enforced patient registration, the number of patients registered in medical marijuana programs across states have increased over time in MML states, particularly after 2009 when there were substantial changes in federal prosecution laws regarding marijuana cultivation, distribution and possession (Fairman, 2016). In addition, registration fees vary widely across MML states (Williams, 2016) Also, research has reported that home cultivation and the presence of dispensaries in MML states have resulted in diversion of marijuana to individuals (Nussbaum et al, 2015; RMHIDTA, 2014; Wirfs-Brock et al, 2010), including youth (Salomonsen-Sautel et al, 2012; Thurstone et al, 2011), who then use it for non-medical purposes.…”
Section: Introductionmentioning
confidence: 99%